2015
DOI: 10.3892/ijo.2015.2943
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ANRIL predicts poor prognosis and promotes invasion/metastasis in serous ovarian cancer

Abstract: Abstract. Recent studies have highlighted the role of long non-coding RNAs (lncRNAs) in carcinogenesis and have suggested that genes of this class might be used as biomarkers in cancer. However, whether lncRNAs are involved in serous ovarian cancer (SOC) remains largely unknown. In the present study, we focused on lncRNA antisense non-coding RNA in the INK4 locus (ANRIL) and investigated its expression pattern, clinical significance, and biological function in SOC. We found that ANRIL levels were elevated in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 32 publications
5
104
0
1
Order By: Relevance
“…ANRIL depletion has been associated with reduced proliferation (28), suggesting a procarcinogenic role supported by overexpression of this lncRNA in various others cancer types (29)(30)(31). In our IBC series, ANRIL overexpression was observed more particularly in the aggressive TNC subtype.…”
Section: Discussionmentioning
confidence: 58%
“…ANRIL depletion has been associated with reduced proliferation (28), suggesting a procarcinogenic role supported by overexpression of this lncRNA in various others cancer types (29)(30)(31). In our IBC series, ANRIL overexpression was observed more particularly in the aggressive TNC subtype.…”
Section: Discussionmentioning
confidence: 58%
“…Increasing evidence indicates that eukaryotic genomes and transcriptomes are the precursors for a number of non-coding RNAs (22), in addition to their established roles as protein-coding genes. Studies have highlighted key regulatory roles of lncRNAs in carcinogenesis and have suggested that some lncRNAs may be potential diagnostic and therapeutic targets in the treatment of OC (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lncRNAs are considered to be dysregulated in gastric,13, 14 colon,12 renal,15 breast16 and ovarian carcinomas 6. Several lncRNAs have been reported to be involved in the initiation and progression of ovarian cancer 17, 18, 19. Therefore, the exploration of the association between ncRNAs and ovarian cancer would be of great value.…”
Section: Introductionmentioning
confidence: 99%